The burden of cardiac diseases in Sub-Saharan Africa - Ntsekhe, Mpiko (SA Heart Journal, 2017)
It is widely acknowledged that sub-Saharan Africa faces a double burden of diseases. On the one hand are the communicable diseases of HIV, tuberculosis and malaria and the other, cardiovascular disease, respectively the commonest and second most common causes of death and disability on the continent.